Effectiveness and safety of Janus Kinase inhibitors in patients with rheumatoid arthritis, results from a multicenter observational “real-life” GIRRCS (Gruppo Italiano di Ricerca in Reumatologia Clinica e Sperimentale) study - Daniela Iacono; Maura Raimondi; Valentina Marino; Flavia Riccio; Maria Laura Marchesano; Alessandra Milone; Addolorata Corrado; Cinzia Rotondo; Ilaria Firenze; Lidia La Barbera; Chiara Rizzo; Simona Montalbano; et al. (Clinical Rheumatology, 2026)
Abstract Objectives To evaluate the “real-life” effectiveness and safety of Janus kinase inhibitors (JAKis) in patients with rheumatoid arthritis (RA) and to analyze the impact of cardiometabolic comorbidities on these outcomes. Methods Patients with RA treated with JAKis were evaluated for disease activity scores, patient-reported outcomes (PROs), and safety in a 12‑month multicenter observational study conducted within the GIRRCS (Gruppo Italiano di Ricerca in Reumatologia Clinica e Sperimentale). Patients were grouped and compared according to the presence of type 2 diabetes (T2D), cardiometabolic multimorbidity (defined as the simultaneous presence of two or more among high blood pressure, T2D, and/or dyslipidaemia), and age ≥ 65 years. Results 440 patients treated with JAKis were included (82.9% female; mean age 61.0 ± 11.0 years); 41.4% had high blood pressure, 39.0% obesity, 28.4% dyslipidaemia, 14.3% T2D, and 3.2% a history of cardiovascular events. A statistically significant improvement was observed in all disease activity measures and PROs over the follow-up period. These improvements seemed to be not influenced by the presence of T2D, cardiometabolic multimorbidity, or age ≥ 65 years. During follow-up, a cumulative adverse events incidence of 18.9% was reported; these were mostly mild and reversible, with no life-threatening events. Drug discontinuation due to adverse events occurred in 7.7% of assessed patients (34 discontinuations due to adverse events). Safety outcomes appeared to be not significantly affected by T2D, cardiometabolic multimorbidity, or age ≥ 65 years. Conclusions In our “real-life” multicenter cohort in patients with RA, JAKis demonstrated effectiveness with an acceptable safety profile despite the relatively short follow-up and the lack of power to assess clinically relevant differences for rare events. The safety profile should therefore be interpreted with appropriate caution. The presence of T2D, cardiometabolic multimorbidity, and age ≥ 65 years did not appear to adversely influence treatment response or safety. Key Points • TJAK inhibitors were effective in reducing disease activity and improving patient-reported outcomes in real-life patients with RA. • Type 2 diabetes, cardiometabolic multimorbidity, and older age did not appear to impair treatment effectiveness of JAK inhibitors in patients with RA. • Most adverse events of JAK inhibitors were mild, reversible, and infrequently led to treatment discontinuation. • These findings may support the use of JAK inhibitors in clinically complex real-life RA populations encountered in daily practice.